CFTR deficiency causes cardiac dysplasia during zebrafish embryogenesis and is associated with dilated cardiomyopathy. (September 2020) - Liu, Yanyan; Lin, Ziyuan; Liu, Mingfeng; Liao, Huijuan; Chen, Yan; Zhang, Xiaohu; Chan, Hsiao Chang; Zhou, Bin; Rao, Li; Sun, Huaqin
Abstract: Mutations in the CFTR gene cause cystic fibrosis (CF) with myocardial dysfunction. However, it remains unknown whether CF-related heart disease is a secondary effect of pulmonary disease, or an intrinsic primary defect in the heart. Here, we used zebrafish, which lack lung tissue, to investigate the role of CFTR in cardiogenesis. Our findings demonstrated that the loss of CFTR impairs cardiac development from the cardiac progenitor stage, resulting in cardiac looping defects, a dilated atrium, pericardial edema, and a decrease in heart rate. Furthermore, we found that cardiac development was perturbed in wild-type embryos treated with a gating-specific CFTR channel inhibitor, CFTRinh-172, at the blastula stage of development, but not at later stages. Gene expression analysis of blastulas indicated that transcript levels, including mRNAs associated with cardiovascular diseases, were significantly altered in embryos derived from cftr mutants relative to controls. To evaluate the role of CFTR in human heart failure, we performed a genetic association study on individuals with dilated cardiomyopathy and found that the I556V mutation in CFTR, which causes a channel defect, was associated with the disease. Similar to other well-studied channel-defective CFTR mutants, CFTR I556V mRNA failed to restore cardiac dysplasia in mutant embryos. The present study revealed an important role for the CFTR ion channel in regulating cardiac development during early embryogenesis, supporting the hypothesis that CF-related heart disease results from an intrinsic primary defect in the heart. Highlights: CFTR acting as an ion channel in regulating embryonic cardiac development CFTR mutant induces embryonic mRNAs change associated with cardiovascular diseases. Channel defect I556V mutation was found in human dilated cardiomyopathy. We support the viewpoint of an intrinsic primary defect in the cystic fibrosis heart.